2016
DOI: 10.3389/fpls.2016.01496
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Management for Enhancing Crop Productivity and Nitrogen Use Efficiency in a Rice-Oilseed Rape Rotation System in China

Abstract: The use of efficient rates of nitrogen (N) fertilizer application is important with regard to increasing crop productivity and maintaining environmental sustainability. Rice-oilseed rape rotations are a mainstay of the economy and food security of China. Therefore, a field experiment was carried out during 2011–2013 in Honghu to identify the most appropriate N application rates for enhancing crop productivity and N use efficiency for rice (Oryza sativa L.)-oilseed rape (Brassica napus L.) rotations. Six N fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 51 publications
7
50
0
1
Order By: Relevance
“…N is an indispensable nutrient for rice growth, and the supply of N strongly regulates rice yield (Yousaf et al, 2016), N absorption and translocation. The chlorophyll content of rice leaves is an active component of N utilization and is closely related to leaf photosynthetic ability (Shiratsuchi et al, 2006; Ata-Ul-Karim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…N is an indispensable nutrient for rice growth, and the supply of N strongly regulates rice yield (Yousaf et al, 2016), N absorption and translocation. The chlorophyll content of rice leaves is an active component of N utilization and is closely related to leaf photosynthetic ability (Shiratsuchi et al, 2006; Ata-Ul-Karim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Khatun et al (2012) and Sampath et al (2013) revealed that stover yield in maize increases with increasing N rate. According to Yousaf et al (2016), for a sustainable crop production continuous renewal of soil fertility through a balance between N demand and supply in cropping systems is important. Guo et al (2016) reported that N is the most yield-restraining nutrient in crop production globally.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has become of foremost importance to select high yielding varieties and genotypes that can uptake and utilize nitrogen more efficiently (Hirel et al, 2001). Efficient nitrogen fertilizer management is essential for achieving economic yields and for enhancing N use efficiency (Pan et al, 2012; Yousaf et al, 2014). Selection of high yielding cultivars is important for food security and growers incomes (Geiger, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield-target-based N fertilization plays an important role when developing profitable and environmentally friendly rice production systems (which is good in environment protection during field production) [4,5]. Accurate and remote in-season estimation of crop N status and its site-specific applications in intensive rice cropping systems is challenging [6]. Rapid, non-destructive, and cost-effective N diagnostic tools are imperative for accurate and timely diagnosis of rice N status at critical growth stages-it is imperative to match N requirements to soil N supply [2,3].…”
Section: Introductionmentioning
confidence: 99%